Research Note: Genetic parameters estimation of egg quality traits in Rhode Island Red and White Leghorn chickens - Xiaoke Zhang; Yunlei Li; Qin Li; Tao Zhang; Yanyan Sun; Fangxiong Shi; Jilan Chen (Poultry Science)
ABSTRACT: The continuous increasing demand for egg quality and quantity, and the expanding market share have enabled the egg industry to achieve significant benefits through genetic improvement. This study aims to estimate the genetic parameters and explore selectable breeding traits in the purebred Rhode Island Red (RIR) and White Leghorn (WL), which are 2 high-yielding layer breeds, and better understand their underlying genetic basis and accelerate genetic progress. The DMU software was utilized to analyze 12 egg quality traits, including egg length (EL), egg width (EW), egg shape index (ESI), egg weight (EWT), albumen height (AH), yolk color (YC), Haugh unit (HU), yolk weight (YW), albumen weight (AW), albumen-to-egg weight ratio (AWR), yolk-to-albumen ratio (YAR), and yolk-to-egg weight ratio (YWR). In RIR, the heritability of egg quality traits ranged from 0.196 to 0.427, while the repeatability ranged from 0.395 to 0.668. In WL, the heritability of egg quality traits ranged from 0.203 to 0.347, and the repeatability ranged from 0.424 to 0.656. In both RIR and WL, highly strong genetic correlations were observed between AW and EW, as well as between AW and EWT. The genetic correlations for AW and EW were 0.902 in RIR and 0.864 in WL, while the genetic correlations for AW and EWT were 0.981 in RIR and 0.960 in WL. The egg quality traits in both breeds showed moderate heritability, indicating great genetic potential for improvement through selective breeding. This can help breeders meet the increasingly diverse egg preferences of consumers through genetic selection. Additionally, there is a highly strong correlation between egg width/egg weight, and albumen weight in both breeds. In practical production, it is feasible to estimate albumen weight by measuring egg width and egg weight, which can simplify the method for measuring albumen weight. In conclusions, our finding provided valuable insights into the genetic architecture of egg quality traits in RIR and WL chickens. They help our understanding of the potential for genetic improvement of these traits through selective breeding programs.